Audiovisual Storytelling in Secondary Schools Located in the Slums of the Buenos Aires Metropolitan Region - Grinberg, Silvia Mariela (2024)
School in postmedia society falls prey to “systemic stupidity” (Stiegler, 2011), while the teacher-cum-coach heeds what is considered the new divine calling for education. In this framework, this video-article looks to elements from research that the author believes might serve as a roadmap for work with words and images in schools that lie beyond that stupidity. Through the audiovisual narratives of students in secondary schools located in a slum in the Buenos Aires Metropolitan Area, the author explores possible approaches to the question of the audiovisual narrative in school and how school is or, rather, can continue to be the repository of the hopes that critical thought harbors. More specifically, the author asks whether audiovisual narratives can contribute to more complex conceptions of the world that help us go beyond the binary logics and infantilization.